PENGARUH FASILITAS, HARGA, LOKASI DAN KELOMPOK REFERENSI TERHADAP KEPUTUSAN WALI MURID MEMILIH JASA PENDIDIKAN SMA MUHAMMADIYAH 1 GRESIK - MUHAMMAD RIFKY PUTRA UTOMO (Program Studi Manajemen Universitas Muhammadiyah Gresik, 2018)
One way to attract parents to send their children to school now is to provide good facilities, easy and affordable access to schools, and parents have a positive perception of school. Parents who want to decide whether to choose education services at a school that suits them have good value and no doubt in choosing education services. The purpose of this study was to analyze and benefit from the results of high school in Indonesia. Muhammadiyah 1 Gresik, to analyze and try the education of guardians who choose education services at Muhammadiyah 1 Gresik High School, to analyze and study the decisions taken by the guardian of choice Students choose education services at Muhammadiyah 1 Gresik High School, to analyze and find parents who choose students from high school education services Muhammadiyah 1 Gresik